LOW-FRICTION DESIGN FOR ENERGY REDUCTION IN CIRCULAR MANUFACTURING PROCESSES - de Borja Dias, Ricardo Garcez (Revista Sistemática, 2021)
This article explores the role of low-friction design as a strategic tool for reducing energy consumption within circular manufacturing systems. While circular economy models typically emphasize recycling, remanufacturing, and material efficiency, the minimization of physical and operational friction has received limited attention. Drawing from tribology and lean manufacturing literature, the study highlights how advanced coatings, lubricants, optimized surfaces, and novel materials can reduce mechanical resistance, while digital tools such as IoT, blockchain, and AI can streamline workflows to eliminate operational inefficiencies. The analysis suggests that integrating low-friction strategies into circular manufacturing may reduce energy consumption by up to 40%, extend equipment lifecycles, and enhance process resilience. The article concludes that bridging tribology with circular economy research is essential to achieving truly energy-efficient and sustainable production systems.